2017
DOI: 10.1002/cbf.3273
|View full text |Cite
|
Sign up to set email alerts
|

Recuperating lung decoction attenuates inflammation and oxidation in cigarette smoke‐induced COPD in rats via activation of ERK and Nrf2 pathways

Abstract: Oxidative/antioxidative imbalance and chronic inflammation are the main contributors to the pathogenesis of chronic obstructive pulmonary disease (COPD). This study evaluated the effect of recuperating lung decoction (RLD) on inflammation and oxidative stress in rats with COPD induced by cigarette smoke and lipopolysaccharides (LPS). We used intravenous infusion of LPS combined with cigarette smoke exposure as a COPD rat model. We observed that RLD treatment increased the protein level of GSH and the ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…COPD is now the fifth leading cause of death worldwide, and it afflicts 15–17 million people in the United States alone [ 16 ]. Although many drugs have been developed and are used to treat COPD, the use of such drugs is limited because of their associated side effects [ 17 ]. There is therefore a growing need for the development of effective new drugs without side effects.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is now the fifth leading cause of death worldwide, and it afflicts 15–17 million people in the United States alone [ 16 ]. Although many drugs have been developed and are used to treat COPD, the use of such drugs is limited because of their associated side effects [ 17 ]. There is therefore a growing need for the development of effective new drugs without side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative/antioxidative imbalance has been recognized as the main contributors to the pathogenesis and carcinogenesis of lung cancer. Mounting evidence suggested that oxidant‐antioxidant imbalance mediated various intracellular and extracellular factors, which were responsible for triggering and promoting impaired antioxidant defense . In this study, we observed that antioxidant NAC of 20 μM and CCE of 80 μg/mL could attenuate 10% CSE‐induced oxidative damage of NHBE cells.…”
Section: Discussionmentioning
confidence: 53%
“…Nuclear erythroid‐related factor 2 (Nrf2), a transcription factor which is responsible for regulating many antioxidant genes and regulates antioxidant defensive mechanism, is regulated negatively by its upstream target Kelch‐like epichlorohydrin‐associated protein 1 (Keap1). Keap1/Nrf2 antioxidant pathway plays an important role in resisting oxidative stress and maintaining a significant redox balance in the body . Our data in this study evaluated the effect of CCE on regulating the transfer of Nrf2 from cytoplasm to nucleus whereas up‐regulating Keap1 expression level in NHBE cells induced by 10% CSE.…”
Section: Discussionmentioning
confidence: 96%
“…Multiple basic researches have showed that smoking is closely related with fibrosis through ERK/MAPK and TGF-Beta/Smad signaling pathways, which play important roles in fibroblast proliferation and collagen expression, leading to capsule fibrosis and tendon adhesion [28,29]. At the final follow-up, the overall trend in our study showed that elbow arthrolysis offers significant improvements in the elbow ROM in both 2 groups, however, we demonstrated that elbow ROM of non-smoking patients was superior to that of smoking patients after elbow arthrolysis in this study.…”
Section: Discussionmentioning
confidence: 99%